Concise and efficient total synthesis of oxyphyllacinol, yakuchione-A and yakuchione-B. Issue 4 (16th February 2022) - Shi, Xiang; Deng, Yu; Kurtz, Nicole C.; Sun, Yue; Xue, Mingxing; Wu, Xian
Abstract: A concise and efficient method for the large-scale total synthesis of oxyphyllacinol (1 ) has been achieved in six steps with an overall yield of 46%. Simultaneously, yakuchione-A (11 ) was obtained in a satisfactory yield (52%) during the process. By employing a Weinreb amide (6 ) as the key masonry block, yakuchione-B (13 ) was also constructed in a great overall yield (56%) and high purity. To overcome the challenges regarding the practical scale, high purity, and reproducibility, the synthetic route that was processed takes advantage of available materials, conventional reactions, and convenient purification methods without using column chromatography. Graphical Abstract: UF0001